CRANIOPHARYNGOMAS IN CHILDREN AND ADOLESCENTS: DIAGNOSTICS AND TREATMENT - E.Yu. Ilyina; N.A. Strebkova; E.S. Kuznetsova; V.A. Peterkova ("Paediatrician" Publishers LLC, 2011)
Craniopharyngoma is a rare embriogenic tumor of sellar or parasellar region with low malignization rates and quite high incidence of relapses. High variability of anatomic localizations makes surgical treatment quite complicated. Regardless satisfactory treatment results and positive outcomes, post-surgical complications may dramatically lower patient's quality of life. Also anatomical localization of craniopharyngomas stipulates high incidence of endocrine disorders. This review contains main diagnostic and treatment principles, complications linked to either tumor growth or to treatment. The authors discuss interpherone α use as a potential treatment method.Key words: craniopharyngioma, hypothalamic obesity, panhypopituitarism. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 67-70.)